2021
DOI: 10.35134/jbe.v6i3.42
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Servant Leadership and Organizational Commitment on Organizational Citizenship Behavior: Job Satisfaction as Mediating Variable

Abstract: The Effect of Servant Leadership and Organizational Commitment on Organizational Citizenship Behavior (OCB) with Job Satisfaction as an Intervening Variable at PT. Karya Semangat Mandiri Padang. This study aims to examine how much influence Servant Leadership and Organizational Commitment to Job Satisfaction and how much influence Servant Leadership, Organizational Commitment and Organizational Citizenship Behavior (OCB) on Job Satisfaction. Methods of data collection through surveys and distributing questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
2
2
0
Order By: Relevance
“…Lastly, indirect-only mediation is found in the role of job satisfaction mediation on servant leadership and organizational citizenship behavior. These findings confirm previous studies (Coetzer et al, 2017; Roza et al, 2021; Ngah et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Lastly, indirect-only mediation is found in the role of job satisfaction mediation on servant leadership and organizational citizenship behavior. These findings confirm previous studies (Coetzer et al, 2017; Roza et al, 2021; Ngah et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…Servant leadership that promotes authenticity, humility, integrity, listening, compassion, responsibility, courage, and altruism, can lead to individual satisfaction and behavior change (Coetzer et al, 2017). Roza et al (2021) and Ngah et al (2021) pointed out that job satisfaction mediates the relationship between servant leadership and organizational citizenship behavior.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…The OCB of employees as seen from the results of this study include how the work environment is concerned with the interests of others by helping each other when work is not completed, how employees try not to complain, how employees are involved in activities that exist in the organization and care about the continuity of organizational work, and how employees carry out activities in compliance with the rules that exist in the organization, namely the KPU Secretariat of the Province of East Kalimantan. The results of this study are also in line with the results of research by Thao & Kang (2020) which state that servant leadership is positively related to OCB and research by Roza et al (2021). So it can be said that employees of serving leaders are more likely to carry out positive behavior towards the organization in line with the leadership style that is consistently applied at the KPU Secretariat of the Province of East Kalimantan.…”
Section: The Direct Influence Of Servant Leadership On Organizational...supporting
confidence: 89%
“…This finding is in compliance with (Trong Tuan, 2017) who confirmed that SL influenced significantly on the OCB. In addition, Roza et al (2021) revealed that SL has a significant influence on OCB. Moreover, (Dulebohn et al, 2012) confirmed that the opinion that leaders behavior directly give an effect on OCB is an old leadership model.…”
Section: Servant Leadership On Ocbmentioning
confidence: 98%